The diets of humpback whales (Megaptera novaeangliae) on the shelf and oceanic feeding grounds in the western North Pacific inferred from stable isotope analysis. Issue 3 (1st November 2012) - Filatova, Olga A.; Witteveen, Briana H.; Goncharov, Anton A.; Tiunov, Alexei V.; Goncharova, Maria I.; Burdin, Alexander M.; Hoyt, Erich
Abstract: Humpback whales feed on a variety of prey, but significant differences likely occur between regional feeding grounds. In this study, the diets of humpback whales were analyzed by comparing stable isotope ratios in animal tissues at three humpback whale feeding grounds in the Russian Far East: Karaginsky Gulf, Anadyr Gulf, and the Commander Islands. Anadyr Gulf is a neritic zone far from a shelf break, Karaginsky Gulf is a neritic zone close to a shelf break, and the Commander Islands represent an open oceanic ecosystem where whales feed off the shelf break. Samples from the Commander Islands had the lowest mean δ 13 C and δ 15 N values (mean ± SE: δ 13 C = −18.7 ± 0.1, δ 15 N = 10.4 ± 0.1) compared to the samples from Karaginsky Gulf (δ 13 C = −17.2 ± 0.1, δ 15 N = 12.7 ± 0.2) and Anadyr Gulf (δ 13 C= −17.8 ± 0.1, δ 15 N = 14.0 ± 0.4). The samples from Anadyr Gulf had the highest δ 15 N values, while the samples from Karaginsky Gulf had the highest δ 13 C values. Both δ 13 C and δ 15 N values differed significantly among all three areas. Our data support the hypothesis that humpback whales tend to feed on fish in neritic areas and on plankton in deep oceanic waters.